1996
DOI: 10.1681/asn.v75667
|View full text |Cite
|
Sign up to set email alerts
|

Arteriolar wall thickening, capillary rarefaction and interstitial fibrosis in the heart of rats with renal failure

Abstract: In experimental renal failure, increased intramyocardial arteriolar wall thickness, reduced myocardial capillary density, and increased cardiac interstitium are found. The extent to which such alterations can be modified by therapeutic interventions has not been investigated to date. The purpose of this study was to examine the effects of Ramipril, Nifedipine and Moxonidine on these structural changes. Sham-operated and subtotally nephrectomized (SNX) 300-g male Sprague-Dawley rats (N = 7 to 11) were left untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(13 citation statements)
references
References 26 publications
1
11
1
Order By: Relevance
“…The finding that cardiac hypertrophy in renal failure can be effectively prevented by the administration of either E or Pc is consistent with the notion that the RAS plays an important role in the regulation of cardiomyocytes cell size and number 6,9,33 and that these changes can be abrogated by therapeutic agents capable of modulating the RAS cascade. 6 The significant attenuation of the heart-to-body weight following E is in line with past observations that demonstrated prevention of the development and progression of LVH with ACEI treatment in uremia.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The finding that cardiac hypertrophy in renal failure can be effectively prevented by the administration of either E or Pc is consistent with the notion that the RAS plays an important role in the regulation of cardiomyocytes cell size and number 6,9,33 and that these changes can be abrogated by therapeutic agents capable of modulating the RAS cascade. 6 The significant attenuation of the heart-to-body weight following E is in line with past observations that demonstrated prevention of the development and progression of LVH with ACEI treatment in uremia.…”
Section: Discussionsupporting
confidence: 85%
“…6 The significant attenuation of the heart-to-body weight following E is in line with past observations that demonstrated prevention of the development and progression of LVH with ACEI treatment in uremia. 33 Paricalcitol also significantly ameliorated myocardial hypertrophy, a novel observation in experimental uremia. Our findings differ from those of Mizobuchi et al 9 who showed only a modest and nonsignificant reduction in cardiac hypertrophy with Pc treatment in uremia.…”
Section: Discussionmentioning
confidence: 94%
“…This finding supports the assumption that the duration of renal replacement therapy has a strong impact on myocardial perfusion, mainly due to rarefication of small intramyocardial vessels. 23 25 We found impaired CFR in 20% of our patients, which is less than reported in other studies 33 and most probably due to the relatively young study cohort. Prior investigations have suggested that CKD is associated with abnormal coronary vasodilator function, 26 which results from multiple mechanisms including decreased capillary density, 27 vascular remodeling, 28 and endothelial dysfunction.…”
Section: Discussioncontrasting
confidence: 72%
“…The hearts of experimental uremic Sprague-Dawley rats (5/6 nephrectomy (5/6 NX)) exhibited cardiac hypertrophy, interstitial fibrosis, and reduced capillary density 47) . Nephrectomy-induced capillary rarefaction in the heart was completely inhibited by the administration of moxonidine, a central sympatholytic agent, but not by the calcium antagonist nifedipine 48) . Another report showed transcript Vegfa reduced in the heart with 5/6 NX, and this was ameliorated with selective renal sympathetic denervation 49) .…”
Section: -5 Chronic Kidney Diseasementioning
confidence: 95%